2016
DOI: 10.1007/s10198-016-0762-9
|View full text |Cite
|
Sign up to set email alerts
|

Competition in the Dutch hospital sector: an analysis of health care volume and cost

Abstract: This paper evaluates the impact of market competition on health care volume and cost. At the start of 2005, the financing system of Dutch hospitals started to be gradually changed from a closed-end budgeting system to a non-regulated price competitive prospective reimbursement system. The gradual implementation of price competition is a ‘natural experiment’ that provides a unique opportunity to analyze the effects of market competition on hospital behavior. We have access to a unique database, which contains h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 30 publications
0
48
0
Order By: Relevance
“…In addition, using a macro budget (i.e. budget restriction on national healthcare expenditure) was suggested as an option to overcome this problem.
If, for example, patients go to the GP more often, perhaps the time for the complex dermato‐oncological patient should, perhaps they should also get more time, so that they are better looked at, and that it in any case doesn't lead to losses. (Dermatologist 9)
It is like if you run a red light and you don't get a ticket you keep running red lights, and if you are not punished for it, you just keep doing your own thing.
…”
Section: Resultsmentioning
confidence: 99%
“…In addition, using a macro budget (i.e. budget restriction on national healthcare expenditure) was suggested as an option to overcome this problem.
If, for example, patients go to the GP more often, perhaps the time for the complex dermato‐oncological patient should, perhaps they should also get more time, so that they are better looked at, and that it in any case doesn't lead to losses. (Dermatologist 9)
It is like if you run a red light and you don't get a ticket you keep running red lights, and if you are not punished for it, you just keep doing your own thing.
…”
Section: Resultsmentioning
confidence: 99%
“…ITCs needed fewer revision surgeries after ACL surgery. In contrast, revision surgery after THR was performed more (14) Abbreviations: ITCs, independent treatment centres; CTS, carpal tunnel syndrome; ACL, anterior cruciate ligament.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, consumers have been able to freely choose their health insurers and healthcare providers. 14,15 In this regulated competition system, health insurers purchase healthcare selectively from different providers, and negotiate features, such as volume, price and quality. Insurers offer 2 types of plans: a benefits in-kind plan and a restitution plan.…”
Section: Introductionmentioning
confidence: 99%
“…This supports our findings. However, the authors also found a drop in average costs for outpatient care (Krabbe-Alkemade et al 2017). Therefore, there might be a difference in how the two sectors were affected by the reforms.…”
Section: Discussionmentioning
confidence: 93%
“…Using DEA-methods, Van Ineveld et al (2015) found that productivity declined significantly in the years 2008-2009 and 2009-2010, but due to the methodology used, causation between deregulation and the productivity loss could not be established. On a restricted database of four specialties, Krabbe-Alkemade et al (2017) evaluated the changes in product volumes, total and average costs of care and the number of activities as a result of the transfer between A-and B-segment in 2008. Similarly to our paper, the variables total and average cost of care were calculated by multiplying the number of registered activities times the average value per activity.…”
Section: Discussionmentioning
confidence: 99%